Effects of cannabidiol in cannabis flower: Implications for harm reduction. (31st August 2021) - Gibson, Laurel P.; Karoly, Hollis C.; Ellingson, Jarrod M.; Klawitter, Jost; Sempio, Cristina; Squeri, Julia E.; Bryan, Angela D.; Bidwell, L. Cinnamon; Hutchison, Kent E.
Abstract: Using a federally compatible, naturalistic at‐home administration procedure, the present study examined the acute effects of three cannabis flower chemovars with different tetrahydrocannabinol (THC) to cannabidiol (CBD) ratios, in order to test whether chemovars with a higher CBD content produce different effects. Participants were randomly assigned to ad libitum administration of one of three chemovars ( THC‐dominant : 24% THC, 1% CBD; THC+CBD : 9% THC, 10% CBD; CBD‐dominant : 1% THC, 23% CBD); 159 regular cannabis users (male = 94, female = 65) were assessed in a mobile pharmacology lab before, immediately after, and 1 h after ad libitum administration of their assigned chemovar. Plasma cannabinoids as well as positive (e.g., high, elation) and negative (e.g., paranoia and anxiety) subjective effects were assessed at each time points. Participants who used the CBD‐dominant and THC + CBD chemovars had significantly less THC and more CBD in plasma samples compared to participants who used the THC‐dominant chemovar. Further, the THC + CBD chemovar was associated with similar levels of positive subjective effects, but significantly less paranoia and anxiety, as compared to the THC‐dominant chemovar. This is one of the first studies to examine the differential effects of various THC to CBD ratios using chemovars that are widely available in state‐regulated markets. Individuals using a THC + CBD chemovar had significantly lower plasma THC concentrations and reported less paranoia and anxiety while also reporting similar positive mood effects as compared to individuals using THC only, which is intriguing from a harm reduction perspective. Further research is needed to clarify the harm reduction potential of CBD in cannabis products. Abstract : Using a naturalistic at‐home administration procedure, this study examined the acute effects of three different forms of state‐legal market cannabis flower. Participants who used the CBD‐dominant and THC + CBD cannabis chemovars displayed significantly lower plasma THC levels relative to participants who used the THC‐dominant chemovar. Further, although the THC + CBD nd THC‐dominant cannabis chemovars were associated with similar levels of positive subjective effects (i.e., high, elation, and drug liking), participants who used the THC + CBD cannabis chemovar reported significantly less paranoia and anxiety.